Estimation of groundwater recharge using neutron probe moisture readings near Golden, Colorado - Poeter, Eileen P., author; Kiusalaas, Nicholas J., author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1992)
To better understand recharge processes under natural conditions in the Denver Basin, a vadose zone monitoring study was conducted from September 1991 through September 1992 at a site near Golden, Colorado. Six access tubes were monitored with a neutron probe to a depth of 8.75 feet to determine moisture profiles several times a month. Moisture characteristic curves were developed for soil samples which were extracted during access tube installation. The van Genuchten function was fitted to experimental moisture characteristic curve data and combined with saturated hydraulic conductivity from laboratory analysis to estimate unsaturated hydraulic conductivity. Numerical analysis based on moisture profiles and hydraulic properties was used to estimate vertical flux.
CWRRI Completion Report No. 165.
November 16, 1992.
Keywords: Groundwater flow -- Colorado -- Golden; Water-supply -- Colorado -- Golden; Seepage